Cognitive data models for sustainable environment - Bhattacharyya, Siddhartha 1975-; Sangaiah, Arun Kumar (Academic Press, 2022)
Cognitive Models for Sustainable Environment reviews the fundamental concepts of gathering, processing and analyzing data from batch processes, along with a review of intelligent and cognitive tools that can be used. The book is centered on evolving novel intelligent/cognitive models and algorithms to develop sustainable solutions for the mitigation of environmental pollution. It unveils intelligent and cognitive models to address issues related to the effective monitoring of environmental pollution and sustainable environmental design. As such, the book focuses on the overall well-being of the global environment for better sustenance and livelihood. The book covers novel cognitive models for effective environmental pollution data management at par with the standards laid down by the World Health Organization. Every chapter is supported by real-life case studies, illustrative examples and video demonstrations that enlighten readers. Explores the development and application of science, engineering and technology in achieving a sustainable lifestyle for humanity Provides tools, connections and proactive solutions to take sustainability programs to the next level Offers perspectives for design, development and commissioning of intelligent applications Provides reviews on the latest intelligent technologies and algorithms related to state-of-the-art methodologies of monitoring and mitigation of environmental pollution.
10. Technical intervention aspects in rural areas. - Includes bibliographical references and index. - Description based on print version record
Keywords: Environmental monitoring -- Data processing; Environnement; Surveillance; Informatique; Environmental monitoring; Data processing